Can We Measure the Individual Prothrombotic or Prohemorrhagic Tendency by Global Coagulation Tests? - Reda, Sara; Morimont, Laure; Douxfils, Jonathan; Rühl, Heiko (Hämostaseologie, 2020)
Hemostasis is a complex process in which abnormalities can cause shifts toward prothrombotic or prohemorrhagic states resulting in thrombosis or bleeding, respectively. Several coagulation tests may be required to characterize these defects but may yet not always reflect a patient's true hemostatic capacity. Thus, global coagulation tests aiming to simulate the coagulation process in vitro instead of measuring single components thereof are certainly of interest to assess prothrombotic or prohemorrhagic tendencies. This review describes the development and application of global coagulation tests, concentrating on the more widely used methods of viscoelastometry and thrombin generation. A focus is placed on conditions characterized by simultaneous changes of various components of hemostasis, such as anticoagulant therapy or hormone-induced coagulopathy, in which global coagulation tests are especially promising. If the key challenges of standardization and automation of these tests are solved, as is the case with automated thrombogram or clot waveform analysis, global coagulation assays will play an important role in the future of laboratory diagnostics of hemostasis and thrombosis.
Keywords: global coagulation tests; hypercoagulability; bleeding; anticoagulant drugs; hormone-induced coagulopathy